POSSÍVEL COMPETIÇÃO ENTRE CANDIDA ALBICANS E PSEUDOMONAS AERUGINOSA EM ÁGUAS DE HEMODIÁLISE. AVALIAÇÃO PRELIMINAR - Simões, M.; Elias, J.C.; Pires, M.F.C. (Revista do Instituto Adolfo Lutz, 2002)
Ver PDF.